Impact of Health Service Quality on Brand Image of Health Facilities - Akbar, Fuad Husain; Zainuddin, Nasaie; S, Senin M.; Jusoh, Juereanor Mat; Feisal, Albert; Ismial, Muhd Feisal; Kok, Heng Han (CENTRAL ASIA AND THE CAUCASUS, 2022)
Objective: This survey aim to determine the impact of the quality of health services on brand image of health facilities in urban and rural areas of Polewali Mandar, West Sulawesi, Province, Indonesia. Materials and Methods: This was observational analytic study with of pilot pathfinder survey design conducted in Polewali Mandar with a total sample 459 people. Data obtained from the distribution of questionnaires to the public. The questionnaire was divided into health service quality questionnaire and the health facility brand image questionnaire. Multiple regression analysis methods: F test, t test, coefficient of determination. Results: Brand image of urban local health facilities has high category's brand image while brand image of health facilities in rural areas was in the low category. Conclusion: All dimensions of health services quality have significant impact on the brand image of the health facilities, except on the nurse dimensions. The brand image of health facilities has highest mean value and the quality of health service has significant influence on the brand image of health facilities